An Analysis of Lexical and Semantic Rhetorical Figures in the Ghazals of Wasil Kabuli - Ibrahimi, Imamuddin; Shafqat, Shafiqullah; Haqiqat, Habibullah (RIRAI Publisher, 2025)
Mirza Muhammad Nabi Wasil Kabuli, one of the great Persian literature poets of Afghanistan, flourished in the late 17th century and ignited the lamp of poetry and literature in his time. He composed very beautiful, attractive, and lively poetry. Both lexical and conceptual rhetorical devices can be found quite extensively in his ghazals. However, his work has not been viewed from this perspective until now. Thus, The general aim of this research is to study thirty selected ghazals of Wasil's Divan in systematic observation of lexical and conceptual rhetorical devices, so that readers become familiar with the elements of his poetry, elements of his verse, and his literary persona. This study is a theoretical study carried out on the library research and analytical-descriptive research method. The subject of our research is Divan of Wasil Kabuli, and the statistical sample of this research consists of thirty ghazals from his Divan of ghazals. The lexical rhetorical device, i.e., parallelism, alliteration, various types of repetition, and balance, and the conceptual rhetorical device, i.e., proportion, contrast, ambiguity, paradox, allusion, synesthesia, conjunction and division, chiasmus, and coordination of qualities, all recur very often in Wasil Kabuli's ghazals and make a contribution to the literary merit of the text along with the potency and joy of the poet's statement.